Backstepping Control for a Five-Phase Permanent Magnet Synchronous Motor Drive - Anissa Hosseynia; Ramzi Trabelsi; Atif Iqbal; Med Faouzi Mimounia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper deals with the synthesis of a speed control strategy for a five-phase permanent magnet synchronous motor (PMSM) drive based on backstepping controller. The proposed control strategy considers the nonlinearities of the system in the control law. The stability of the backstepping control strategy is proved by the Lyapunov theory. Simulated results are provided to verify the feasibility of the backstepping control strategy.